A Comparative study of total harmonics distortion between Spwm and She-Pwm modulation techniques for inverters. - Aboadla, Ezzidin Hassan Elmabrouk; Tohtayong, Majdee; Aznan, Khairil Azhar; Khalil, Ashraf; Khan, Sheroz; Habaebi, Mohamed Hadi; Gunawan, Teddy Surya; Hamida, Belal Ahmed; Yaacob, Mashkuri (Faz Publishing, 2019)
Power Converters are basically used to convert one level of DC or AC level to another level and for the DC-AC Inverters used to convert renewable sources DC, like solar energy or storage batteries into AC power. When converting the DC to AC, the output level voltage may contain unwanted harmonics distortion due to the switching. These switching techniques are various number of modulation schemes employed to control ON-OFF the switching of IGBT (or MOSFET) of Inverters and to reduce these harmonics effectively. The most commonly used for the modulation methods are Sinusoidal Pulse Width Modulation (SPWM) and Selective Harmonics Elimination Pulse Width Modulation (SHE-PWM). These are two paramaters that are commonly used in those two modulation techniques and it is modulation index and the number of pulses. As a result the minimum Total Harmonic Distortion (THD) is used as a criterion for comparing results by both techniques. This paper demonstrates the comparison between SPWM and SHE-PWM implemented in the unipolar inverter. To assess and validate the utility of the techniques, simulation results are obtained using MATLAB software.